Floating Car Data als Quelle für Echtzeit-Verkehrsdaten. - Haspel, Ulrich; Nöth, Frederik (Deutscher Verkehrs-Verl., 2007)
Nutzung von Floating Car (FC)-Daten verfolgt das Ziel, neben den bisherigen Querschnittsmessungen mobile Verkehrsinformationen direkt aus dem Verkehrsfluss heraus zu ermitteln. Dadurch werden Verkehrsprognosen in Echtzeit möglich, wie sie zur Optimierung bei der Routenplanung oder zum Flottenmanagement verwendet werden können. difu

Complementary to the existing techniques of data assessment, the Floating Car Data facility allows traffic-related information - based on real time traffic flow data - to be ascertained directly. A procedure was adopted in Nuremberg whereby 500 taxis were fitted with GPS and wireless facilities to assess current traffic situations along major roads. Access to the internet address www.nuernbergverkehr.de allows both the journey times (calculated with the help of analysis-focused software programmes) along main roads plus the actual traffic situation to be called up instantly. In Germany, for the first time ever, actual traffic-related information is being offered that covers a fairly wide area of a given city's pattern of trunk roads. It has thus been possible to show that the FCD facility suitably complements the existing methods of data assessment. In future, should the need arise to replace them, the penetration ratio (vehicles equipped with FCD sensors) will have to be greatly increased. difu
Keywords: Verkehr; Verkehrsplanung; Straßenverkehr; Verkehrsmittel; Verkehrsablauf; Verkehrsprognose; Informationstechnologie; Verkehrsinformation; Verkehrsdaten; Taxi; Ortung; Einsatzplanung; Projektbeispiel; Monitoring